2010
DOI: 10.1074/jbc.m109.091611
|View full text |Cite
|
Sign up to set email alerts
|

S-Nitrosylation Regulates Nuclear Translocation of Chloride Intracellular Channel Protein CLIC4

Abstract: Nuclear translocation of chloride intracellular channel protein CLIC4 is essential for its role in Ca2؉ -induced differentiation, stress-induced apoptosis, and modulating TGF-␤ signaling in mouse epidermal keratinocytes. However, post-translational modifications on CLIC4 that govern nuclear translocation and thus these activities remain to be elucidated. The structure of CLIC4 is dependent on the redox environment, in vitro, and translocation may depend on reactive oxygen and nitrogen species in the cell. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
38
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 51 publications
3
38
0
Order By: Relevance
“…For instance, the NO-dependent S-nitrosylation of GAPDH enables its binding to the E3-ubiquitin-ligase Siah, which translocates GAPDH to the nucleus (Hara et al 2005). Malik et al (2010) have recently reported that S-nitrosylation induces the nuclear translocation of the keratinocytes Chloride Intracellular Channel protein (CLIC4), being this mechanism independent of the NO-cGMP pathway. Thus, it will be very interesting to investigate if nuclear translocation of UVR8 may be influenced by UV-B-induced NO production.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the NO-dependent S-nitrosylation of GAPDH enables its binding to the E3-ubiquitin-ligase Siah, which translocates GAPDH to the nucleus (Hara et al 2005). Malik et al (2010) have recently reported that S-nitrosylation induces the nuclear translocation of the keratinocytes Chloride Intracellular Channel protein (CLIC4), being this mechanism independent of the NO-cGMP pathway. Thus, it will be very interesting to investigate if nuclear translocation of UVR8 may be influenced by UV-B-induced NO production.…”
Section: Discussionmentioning
confidence: 99%
“…However, the modified protein migrated faster than full-length CLIC4, suggesting that it was prone to degradation. This is likely a consequence of the conformational change induced in the protein (13). iNOS knockout macrophages stimulated with LPS and IFNγ also showed reduced CLIC4 nuclear translocation ( Fig.…”
Section: Resultsmentioning
confidence: 98%
“…CLIC4 nuclear translocation is regulated by NOS activity through direct modification of a CLIC4 cysteine residue by NO (13), and nuclear CLIC4 functions to enhance TGF-β signaling (8), the latter being a critical modulator of macrophage deactivation (17). Stimulation with LPS and IFNγ induces Snitrosylation of CLIC4 in macrophages as detected by a biotin switch assay (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations